PENURUNAN NYERI LUTUT LANSIA DENGAN LATIHAN STRETCHING DI PANTI WREDHA DHARMA BHAKTI SURAKARTA - Noorratri, Erika Dewi; Hartutik - STIKES ?Aisyiyah Surakarta, Sri (IJMS - Indonesian Journal on Medical Science, 2020)
Abstract: Elderly is the final stage of the human life cycle, which is a part of the life process that cannot be realized and will be experienced by every individual in the world. The effect on the aging process can cause various problems. These problems include biologically, mentally, and economically. In the elderly who experience physical deterioration due to the aging process can be prevented by doing various components of exercise. Components of exercise in the elderly can be given with flexibility or stretching exercises in the elderly. Many elderly people at Surakarta Dharma Nursing Home suffer knee pain. Pain in the knee can be reduced by stretching exercises. Objective: To analyze the decline in elderly knee pain with stretching exercises at the Dharma Bakti Surakarta nursing home. Method: Quasi Experimental method. The study design was pre-post group test design with control group. The research sample consisted of 18 treatment groups and 18 control groups. Results: showed that in the elderly treatment group there was a significant decrease in knee pain from the first meeting to the sixth, with a value of p = 0,000 (p <0.05). The stretching exercise treatment significantly decreases knee pain in the elderly, the control treatment does not significantly reduce knee pain in the elderly and the treatment of stretching exercises is better at reducing knee pain in the elderly than the control. Conclusion: The stretching exercise treatment significantly influences knee pain in the elderly.Keywords: Stretching, knee pain, elderly Abstrak :  Lansia merupakan tahap akhir dari siklus hidup manusia, dimana merupakan bagian dari proses kehidupan yang tidak dapat disadari dan akan dialami oleh setiap individu di dunia. Pengaruh pada proses menua dapat menimbulkan berbagai masalah. Masalah tersebut diantaranya baik secara biologis, mental, maupun ekonomi. Pada lansia yang mengalami kemunduran secara fisik akibat proses penuaan dapat dicegah dengan melakukan berbagai komponen latihan. Komponen latihan pada lansia dapat diberikan dengan latihan fleksibilitas atau peregangan pada lansia. Lansia di panti wredha dharma bhakti Surakarta banyak yang mengalami nyeri pada lutut. Nyeri pada lutut dapat diturunkan dengan latihan stretching. Tujuan Penelitian : Menganalisis penurunan nyeri lutut lansia dengan latihan stretching di panti wredha Dharma Bakti Surakarta. Metode: metode Quasi Eksperimental. Rancangan penelitian pre-post group test design with control group.sampel penelitian ada 18  kelompok perlakuan dan 18 kelompok kontrol. Hasil: menunjukkan bahwa pada kelompok perlakuan lansia terjadi penurunan nyeri lutut secara signifikan dari pertemuan pertama sampai keenam, dengan nilai p=0,000 (p< 0,05). Perlakuan latihan stretching secara signifikan berpengaruh menurunkan nyeri lutut pada lansia, perlakuan kontrol tidak signifikan menurunkan nyeri lutut pada lansia dan perlakuan latihan stretching lebih baik dalam menurunkan nyeri lutut pada lansia dibandingkan kontrol. Kesimpulan: Perlakuan latihan stretching secara signifikan berpengaruh signifikan menurunkan nyeri lutut pada lansia.Kata Kunci : Stretching,  nyeri lutut, lansia